Completed Suicide With Violent and Non-violent Methods by the Elderly in Rural China: A Psychological Autopsy Study - Zhu, Rong-Ting; Ma, Zhen-Yu; Jia, Cun-Xian; Zhou, Liang (Frontiers in Psychiatry, 2021)
Background: Late-life suicide is a severe public health problem in rural China; however, knowledge regarding the specific characteristics and risk factors for completed suicide via violent and nonviolent methods among elderly individuals in rural China is limited. Methods: Subjects aged 60 years or older were selected from rural areas in Shandong, Hunan, and Guangxi provinces in China. This study was a 1:1 matched case-control design conducted by using the psychological autopsy method. Results: According to the univariate analyses, the presence of mental disorder, higher degree of depression, loneliness, lack of social support, hopelessness, impulsivity, and increased quantity of life events were associated with suicide in both violent and nonviolent methods. For violent suicide, another risk factor was the lack of pesticides at home. For nonviolent suicide, other risk factors were not currently married, family suicide history, and alcohol use disorder (P < 0.05). Variables that remained in the logistic regression model were the severity of depressive symptoms for both violent and nonviolent suicide. For nonviolent suicide, the degree of hopelessness was another independent risk factor. In addition, violent suicides were more likely to lack pesticides at home, choose the spring season and have an increased quantity of life events than those who died by suicide via nonviolent methods. Conclusion: The major risk factor for both violent and nonviolent suicide was the severity of depressive symptoms. Suicide prevention measures that focus on depression among this vulnerable population are urgently needed. Moreover, the characteristics of suicides via violent methods differed from those via nonviolent methods among elderly individuals. Suicide prevention efforts should be tailored to the specific characteristics of the different suicide methods utilized by older adults in rural areas.